Research on corporate social responsibility: Insights and future directions - Buthiena Kharabsheh; Hussam A. Al-Shammari; Khaled Bataineh (Administrative Sciences, 2023)
Our current review paper aims to discuss the various issues pertaining to the future research avenues of CSR, and possible expansions that this scholarly field could have considering the growing interests from numerous academic disciplines and practitioners across the globe. In particular, we briefly discuss the work that has been performed on CSR, major theories that guided this area of research, and a summary of prior research findings. Then, we suggest future directions on specific drivers that motivate firms to engage in CSR activities. Specifically, we provide insights on how research should focus on within-firm variables, namely personality traits of TMTs and their possible impact on their firms' stances towards CSR. We also briefly discuss the need for more advanced method of CSR rankings that takes into account consumers' perception about the existing CSR rankings, such as KDL, and also consumers' satisfaction and responses towards firms' CSR. Finally, we highlight the need for two separate measurements of CSR; a measure that speaks to external stakeholders of the firm, and another measure that speaks to the internal stakeholders of the firm.
Keywords: 350; literature review; corporate governance; corporate social responsibility; CSR measurement